Pemerolehan Informasi pada Alkitab Berbahasa Indonesia Menggunakan Metode BM25 dan Query Expansion Word2Vec - Pretty Natalia Hutapea; Putra Pandu Adikara; Yuita Arum Sari (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
The Indonesian state officially recognizes six religions, namely Islam, Protestantism, Catholicism, Hinduism, Buddhism, and Confucianism. In Protestantism, the Bible is used as its holy book. In carrying out their worship, Protestants must have a close relationship with God through reading and studying the Bible. A Bible book contains a lot of information, so a system is needed to access and manage that information quickly and accurately. The information retrieval system can be used to get results relevant to user needs through query input. Queries entered by the user sometimes do not return relevant results due to errors in the query, so a query expansion technique that is capable of expanding or modifying the query is required. The modeling used for query expansion is Word2Vec, while to obtain relevant document results, the document is ranked using the Best Match 25 (BM25) method. Tests conducted in this study compared the document output when using query expansion and without using query expansion. The test results of this study get the highest results when not using the query expansion with the Precision @ 10 and MAP values ​​of 0.86 and 0.93.